Tick Sweats - Arnsperger, Alyssa; Fatehi, Soheila; Park, Yoonseong (My University, 2018)
Ticks are obligatory ectoparasites of many vertebrate hosts including human. Osmoregulatory functions of ticks are crucial for the survival, especially, in the off-host ticks in arid area. We found that injection of water in the body cavity of tick immediately triggers excretion of solution through the exoskeletal cuticles, like sweating. This response occurred in a bilateral asymmetric manner; the injection on left side of the body induced the sweating on only the left half, while the injection into right side did not induce sweat. The sweating response was reduced in the injections of high osmolar Naci (1 M). This is the first description of sweating physiology in maintenance of water homeostasis in the Lone star tick.
Keywords: Fall 2018